2012
DOI: 10.1353/arw.2012.0039
|View full text |Cite
|
Sign up to set email alerts
|

Pastoral Production in Colonial Kenya: Lessons from the Past?

Abstract: Abstract:This article examines the troubled course of attempts to modernize and control pastoral production in Kenya over the last hundred years. It begins with an overview of changes in pastoralism to provide context and then gives more detailed consideration to the failure of colonial attempts to manage livestock resources. Finally, it discusses recent developments in relation to the past. It argues that study of pastoralism's past offers valuable lessons and provides insights into its present and possible f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“…The settlers slowly demarcated the land, cut down some of the indigenous trees and bushes to build their houses and to pave way for a fertile piece of land to cultivate (Waller, 2012). The Agikuyu people and some of the Maasai pastoralists were pushed to the Northern edge of Kiambu West near Aberdare and Lari forests.…”
Section: Implications Of Colonial Land Alienation On the Awiks On Foomentioning
confidence: 99%
See 3 more Smart Citations
“…The settlers slowly demarcated the land, cut down some of the indigenous trees and bushes to build their houses and to pave way for a fertile piece of land to cultivate (Waller, 2012). The Agikuyu people and some of the Maasai pastoralists were pushed to the Northern edge of Kiambu West near Aberdare and Lari forests.…”
Section: Implications Of Colonial Land Alienation On the Awiks On Foomentioning
confidence: 99%
“…One of the respondents (Muraya O.I 2017) claimed "The Europeans were being asked to keep their cattle at home but they never gave attention to whatever they were being told". Hobley (1967) & Waller (2012 further observed that in the initial stage of settlement in the squatter and reserve land, the squatters were not entirely detribalized. Those of the first generation of squatters or initial land owners in squatter land continued fairly well with their traditional…”
Section: Implications Of Colonial Land Alienation On the Awiks On Foomentioning
confidence: 99%
See 2 more Smart Citations
“…In so doing, local resource control was significantly restricted and pastoralist and agricultural groups were disenfranchised or at times relocated into reserves. Land tenure challenges in Kenya's group ranches since their creation in the 1970s have been detailed extensively elsewhere, including trends toward privatization and sub-division (Galaty 1994;Mwangi 2007;Western et al 2009;Waller 2012). Community members in Laikipia face similar land tenure challenges as other pastoralists in Kenya.…”
Section: Introductionmentioning
confidence: 99%